UJI BEDA FAKTOR PENDIDIKAN DAN STATUS PENYULUH TERHADAP TINGKAT PERANAN PENYULUH PERTANIAN DI KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - Miranda Romaully; Hamidah Hamidah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
This study aimed to analyze the differences of education and the status of agricultural extension  for farmers perception of the level of extension role in Sungai Pandan Hulu Sungai Utara. The study uses primary data from 44 farmers respondents by questionnaire to know their perceptions of the role of educator then tested the difference between education level by college and non-collage as well as the status of civil servants and THL-TBPP with MANOVA analysis used Minitab software. Differences in education level and status counselor has a relationship with the farmer answers about their  perceptions of the average level of the role of agricultural extension in Sungai Pandan Hulu Sungai Utara. At least there is farmer who responded more positively to the extension status of civil servants and collage educated. Or at least there is one factor extension status and level of education showed differences in the perception of farmers to the average level of the role of agricultural extension.